Reference Ranges of Fetal Cerebral Lateral Ventricle Parameters by Ultrasonography - Aderemi Ishola; Christianah Mopelola Asaleye; Oluwagbemiga Oluwole Ayoola; Olabisi Morebise Loto; Bukunmi Michael Idowu (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Objectives This study was done to evaluate the normal fetal cerebral lateral ventricle dimensions with transabdominal ultrasonography. The atrial width (AW), ventricle-tochoroid measurement (V-C), ventricle-to-hemisphere ratio (VHR), and combined anterior horn measurement (CAHM) were taken. Methods This was a cross-sectional study involving 400 normal singleton pregnant subjects whose gestational ages were between 14 and 40 weeks. Transabdominal sonography was performed to obtain the values of the fetal cerebral lateral ventricle (FCLV) parameters. Data were reported as mean standard deviation (SD) for continuous variables. The degrees of correlation between FCLV parameters and the estimated gestational age (EGA) were obtained using Pearson's correlation. Regression equations were used to generate the reference limits for the FCLV measurements. Results The values of AW, V-C measurements and CAHM increased with advancing gestation. The mean values of the AW, V-C and CAHM from 14 to 40 weeks increased from 6.60 0.94 mm to 9.75 0.07 mm (R2 = 0.114), 0.80 0.00 mm to 1.90 0.14 mm (R2= 0.266), and 6.95 0.06 mm to 23.07 4.02 mm (R2= 0.692) respectively, while the mean VHR decreased from 61.20 1.60% to 42.84 2.91% (R2 = 0.706) over the same period. Conclusion The AW, V-C, and CAHM increase, while VHR decreases with advancing gestation.